Impact of antibiotic choice on readmission in adults experiencing an acute COPD exacerbation. (30th September 2020) - Lancaster, Jason W; McAuliffe, Laura; O'Gara, Elizabeth; Cornelio, Cyrille; Hum, Jennifer; Kim, Yestle; Phung, Ann; She, Kevin; Lei, Yuxiu; Balaguera, Henri; Liesching, Timothy
Abstract: Purpose: The impact of antibiotic therapy in managing acute chronic obstructive pulmonary disease (COPD) exacerbations requiring hospitalization remains unclear. We conducted a study to assess the impact of antibiotic therapy on the rate of 30-day readmission after discharge from a hospital stay for an acute COPD exacerbation. Additional study outcomes analyzed included the effects of antibiotic therapy on hospital length of stay, in-hospital mortality, 90-day and 12-month readmission rates, and time to next COPD exacerbation. Methods: The study was an institutional review board–approved, retrospective, observational review of adult patients at a tertiary academic medical center. The medical records of patients 18 years of age or older who were hospitalized for an acute COPD exacerbation between January 2008 and December 2014 were evaluated. Included patients were stratified by receipt of guideline-appropriate, guideline-inappropriate, or no antibiotic therapy. Nonparametric data were analyzed using the Kruskal-Wallis test (nonparametric) and categorical data via χ 2 test, respectively. Results: Three hundred twenty-five subjects were included; there were no significant differences in baseline characteristics in the 3 study groups. Sixty-eight percent of patients ( n = 223) received antibiotics. The percentage of patients readmitted within 30 days did not differ between cohorts: 11.9% (appropriate therapy) vs 13.2% (nonappropriate therapy) vs 12.2% (no antibiotics) ( P = 0.95 for all comparisons). Additionally, no detectable differences in 90-day or 12-month readmission rate, length of hospital day, or in-hospital mortality were found. However, a trend toward increased time to next COPD exacerbation was noted in those receiving antibiotics vs no antibiotics (352 days vs 192 days, P = 0.07). Conclusion: Treatment of COPD exacerbations with antibiotics did not impact readmission rates, length of hospital stay, in-hospital mortality, or time to next exacerbation. More investigation is warranted to assess the effect of antibiotics on time to next exacerbation, as well as comparative effectiveness between antibiotic classes.